ANALISIS FAKTOR YANG MEMPENGARUHI MINAT PENGGUNAAN QRIS SEBAGAI METODE PEMBAYARAN PADA MASA PANDEMI - Supriyanto Supriyanto; Ahmad Fahri Syaifuddin Kurnia Rahman (Indonesian Scientific Journal of Islamic Finance, 2022)
QRIS is a QR code-based payment standard set by Bank Indonesia to support and facilitate digital payments in Indonesia, as an effort to encourage the realization of an integrated payment system. The purpose of this study was to determine the factors that influence student interest in using QRIS as a payment method during the covid-19 pandemic. The independent variables in this study are knowledge (X1), benefits (X2) and risks (X3) and interest (Y) as the dependent variable. The research method used is quantitative method with primary data sources obtained directly through questionnaires. The population of this research is the students of UIN Raden Mas Said Surakarta, totaling 15,858 respondents, with a sample of 100 respondents who were taken using purposive sampling technique. The data collected was then analyzed using multiple regression analysis models through the SPSS 22 application. The results showed that the variables Knowledge (X1), Benefits (X2), and Risks (X3) simultaneously had a positive and significant effect on student interest in using QRIS (Y). Based on the results of multiple linear regression analysis, the equation Y = -0.790 + 0.571 X1 + 0.305 X2 + 0.153 X3 + e, from the three variables it can be concluded that the knowledge variable has the greatest influence, which is 57,1%.